Comparison of colorimetric MTT and clonogenic assays for irradiation and cisplatin treatment on murine fibrosarcoma SA-1 cells - Čemažar, Maja (Radiology and oncology (Ljubljana), 1999)
Background. The aim of our study was to determine the relationship between cell survival of SA-1 tumor cells measured by clonogenic assay and MTT assay after irradiation and cisplatin treatment. Materials and methods. Survival of SA-1 cells was measured after irradiation (2-8 Gy) and cisplatin treatment (0.05-0.5 u g/ml) by clonogenic assay performed 7 days after treatment, and byMTT assay performed on day 3, 4, 5, and 7 after the treatment. Results. The results showed good correlation between MTT assay and clonogenic assay for irradiation doses below 4 Gy. For higher doses good correlation between MTT and clonogenic assay was determined only when MTT assay was performed on day 5and 7 after the treatment. In the case of cisplatin treatment, similar pattern was observed, good correlation between IC50 values for MTT and clonogenic assay was found when MTT assay was performed on day 5 and 7 after the treatment. Conclusion. Results of our study confirmed the results of previous studies addressing this topic and further support the use of MTT testas an alternative test for clonogenic test as a predictive assay of tumourresponse to the radio or chemotherapy.
Keywords: Cisplatin; Colorimetry; Drug therapy; Fibrosarcoma; Mice; Radiotherapy; Sarcoma, experimental; Tetrazolium salts; Tumor stem cell assay